From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Postglacial fault movement and palaeoseismicity in western Scotland: A reappraisal of the Kinloch Hourn fault, Kintail - Iain S. Stewart; Callum R. Firth; Derek J. Rust; Philip E.F. Collins; Judith A. Firth (Journal of Seismology, 2001)